The artist as citizen - Polisi, Joseph W. (Cambridge Amadeus Press, 2005)
The Artist as Citizen is a compilation of Joseph W. Polisi's articles and speeches from his two-decade tenure as president of the Juilliard School. His writings focus on the role of the artist in American society as a leader and communicator of human values. The extended prologue includes Polisi's recollections of his early days at Juilliard and the selection process that resulted in his appointment as the school's sixth president. Also included is a discussion of the important role that Juilliard plays in the workings of Lincoln Center. Polisi makes a strong point that "there should be no dividing line between artistic excellence and social consciousness." He contends that the traditional "self-absorbed artist" is the wrong model for the arts in America in the 21st century.